Construction and application of full-process intelligent venous thromboembolism prevention and control platform (全流程智能化静脉血栓栓塞症防控平台构建与应用) - LIU Qian (刘倩); LIU Wei (刘维); GUO Mengjie (郭梦洁); GUO Fangsu (郭芳素); LI Yunge (李昀阁); FENG Yifan (冯依凡); WANG Wuhua (王武化) (中西医结合护理)
Venous thromboembolism (VTE) prevention is a key indicator for quality evaluation of hospital care. This paper summarized the construction and practice of full-process intelligent VTE prevention and control platform in perspectives of risk assessment and intelligent filling, AI predictive modeling, quality control, Disease-specific databases, follow-up applications, and provided reference for VTE prevention and treatment in the hospital. (静脉血栓栓塞症(VTE)规范化预防是评价医院医疗质量的重要指标。本研究阐述全流程智能化VTE防控平台构建过程中关于风险评估智能填充、AI预测模型构建、质控管理、专病数据库建立、随访小程序实施等的成效与经验, 以期为医院构建完善的VTE防治管理方案提供参考。)